Effects of leaf removal and shoot trimming performed in different periods on cv. Vermentino - Conti, Filippo (2019)
Mestrado em Engenharia de Viticultura e Enologia (Double Degree) / Instituto Superior de Agronomia. Universidade de Lisboa / Faculdade de Ciências. Universidade do Porto